The Effect of Work First Job Placements on the Distribution of Earnings: An Instrumental Variable Quantile Regression Approach - Autor, David H.; Houseman, Susan N.; Kerr, Sari Pekkala (Journal of Labor Economics, 2017)
Government employment programs for low-skilled workers typically emphasize rapid placement of participants into jobs, of which many are temporary-help jobs. Using data from Detroit’s welfare-to-work program and the Chernozhukov-Hansen instrumental variables quantile regression method, we find that neither direct-hire nor temporary-help job placements significantly affect the lower tail of the earnings distribution. In the upper tail, direct-hire placements yield sizable earnings increases for over half of participants, while temporary-help placements yield significant earnings losses at higher quantiles. Our results cast doubt on the efficacy of employment programs’ exclusive focus on rapid job placement and their widespread reliance on temporary-help placements.